Water-soluble benzoselenadiazole-based conjugated polymer fluorescent sensor with high selectivity for ferric ions and mercury ions and possible applications as integrated molecular logic gates. Issue 21 (27th May 2015) - Lei, Yunxiang; Li, Hui; Huang, Xiaobo; Chen, Jiuxi; Liu, Miaochang; Gao, Wenxia; Ding, Jinchang; Lin, Dajie; Wu, Huayue
Abstract: A conjugated polymerP-1 based on benzoselenadiazole was synthesized by the polymerization of 1, 4-bis[3′-( N, N -diethylamino)-1′-oxapropyl]-2, 5-diiodobenzene (M-1 ) and 4, 7-diethynylbenzoselenadiazole (M-2 ) via Pd-catalyzed Sonogashira–Hagihara coupling reaction. The water-soluble conjugated polyelectrolyteP-2 was obtained by the reaction ofP-1 with ethyl bromide. The responsive optical properties ofP-1 andP-2 on various metal ions were investigated by fluorescence spectroscopy in real-time detection.P-1 showed highly sensitive and selective detection of Fe 3+ by 'turn-on' fluorescence enhancement in DMSO/H2 O.P-2 exhibited outstanding sense of Hg 2+ usingBSe as receptor by 'turn-off' fluorescence quench type and Fe 3+ using unionized triethylamino group as receptor by 'turn-on' fluorescence enhancement type in MeOH/H2 O, respectively. Additionally, the addition of EDTA to theP-2 –metal complexes could result in the fluorescence recovery of theP-2 solution. Fluorescence spectral responses as output signals and two independent molecular input signals based onP-2 could be used to demonstrate important logic operation like INHIBIT and IMPLICATION gates. Graphical abstract: